Increased perinatal intracranial pressure and prediction of early puberty in girls with myelomeningocele. Issue 1 (July 1996) - Proos, L A; Dahl, M; Ahlsten, G; Tuvemo, T; Gustafsson, J
Abstract : An increased risk of developing precocious puberty has been reported in children with myelomeningocele. In order to evaluate this further and to study factors associated with early or precocious puberty the medical records of all girls with myelomeningocele, born from 1970 onwards (n = 64), who were admitted to our unit were reviewed. Early/precocious puberty (E/PP) was defined as breast development or pubic hair corresponding to Tanner stage 2 before the age of 9.2 years. In 32 out of 62 cases data were sufficient for evaluation of the timing of puberty. Twenty girls had E/PP and 12 girls normal timing of puberty. In the girls who had reached the age of 9.2 years the incidence of E/PP was at least 52%. Girls with E/PP had a higher incidence of hydrocephalus, were treated with intraventricular shunts more often, and had significantly higher frequency of increased intracranial pressure during the perinatal period (p < 0.05, p < 0.01, and p < 0.001, respectively). The group of girls developing E/PP was also more severely disabled with respect to motor and urological function and had more shunt revisions. In conclusion, E/PP in girls with myelomeningocele is strongly associated with increased intracranial pressure particularly during the perinatal period.